The Role of Nrf2 in the PM-Induced Vascular Injury Under Real Ambient Particulate Matter Exposure in C57/B6 Mice - Gao, Mengyu; Ma, Yuanyuan; Luo, Jing; Li, Daochuan; Jiang, Menghui; Jiang, Qixiao; Pi, Jingbo; Chen, Rui; Chen, Wen; Zhang, Rong; Zheng, Yuxin; Cui, Lianhua (Frontiers in Pharmacology, 2021)
Short- and long-term exposure to particulate matter (PM) has been associated with cardiovascular disease (CVD). It is well recognized that oxidative stress is a potential major mechanism in PM-induced vascular injuries, in which the nuclear factor E2-related factor 2 (Nrf2) signaling pathway plays a critical role. In the current study, a Nrf2 knockout mouse model was used in combination with an individual ventilated cage (IVC)-based real-ambient PM exposure system to assess the potential vascular injury and the potential role of Nrf2 in the angiotensin II (Ang II)-associated vascular injury. After 6- or 11-weeks exposure to PM, the histopathology assay revealed that PM exposure resulted in the thickening of the walls of vascular. After 6 weeks exposure to PM, the ELISA assay revealed that PM exposure resulted in the elevated plasma concentration of Ang II. The expression levels of genes of interest were then further investigated with quantitative real-time PCR. Notably, the results showed that Angiotensinogen (AGT), Angiotensin converting enzyme (ACE) and Angiotensin type I receptor (AT1R) were involved in PM-induced pathological changes. Western blotting for ACE showed similar results. Moreover, the extent of vascular thickening and the Ang II elevation was most prominent in the Nrf2 gene knockout PM exposure group (KOE). Furthermore, the expression of Nrf2 downstream relevant genes (HO1, Nqo1, Gclc, Gsta4) were significantly enhanced in the wildtype PM exposure group (WTE) , while those were remarkably suppressed in the Nrf2 gene knockout groups. The ELISA result of MCP-1 protein serum levels in the KOE group was significantly higher in relation to that in the Nrf2 knockout control group (KOC). In summary, PM exposure is associated with thickening of vascular wall, while Nrf2 knockout may further enhance this effect. A potential mechanistic contributor of such effects is the activation of ACE/ANGII/AT1R axis, in which Nrf2 played a regulatory role.